Occurrence of Heavy Metal in Green Coconut Water and Surface Seawater of the Sea Beach Areas of Bangladesh - Monsur Ahmad; Md Junayed; Md. Rahim Badsha; Md. Fahad Bin Quader; Shamsul Morshed (Health Dynamics, 2024)
Background: Green coconut water is a most popular functional drink in all tropical countries. The presence of toxic heavy metals in surface seawater is a major problem globally, with a large share in developing countries like Bangladesh. The objective of the study was to assess the concentration of heavy metals like Pb, Cr, Ni, Cu, and Cd in green coconut water and surface seawater around sea beach areas of Bangladesh. Methods: Green coconut water and surface seawater samples were collected from six sea beach areas and transferred to the laboratory. Then, they were allowed for digestion, and finally, the concentration of heavy metal was assessed by the atomic absorption spectrophotometer (AAS). Results: In green coconut water, the concentrations of heavy metal exist bellowing the safe limit with the following order: Pb > Cr > Cu > Ni > Cd. But, Pb, and Cr were prevalent in surface seawater and found to decrease in a sequence of Pb > Cr > Ni > Cd, Cu. Besides, Human health risks associated with the intake of these metals were evaluated in terms of metal pollution index (MPI), daily intake of metals (DIM), health risk index (HRI), and hazard index (HI). However, most of the index values were found to be bellowing the reference value. Conclusion: The concentration of green coconut water is almost proportional to surface seawater in sea beach areas. The high prevalence of Pb and Cr in surface seawater is alarming, and this impact is already seen in green coconut water. So, it is necessary to take action on seawater pollution in Bangladesh.